Interventionism and abstention during childbirth - Franco G., Rodrigo (2015)
Agreement and in collaboration with professors of the Department of Obstetrics and Obstetrical Clinic, Drs. Irrigation Manuel Gonzalez Perez and Felix Retes, we wanted to bring to this gathering of distinguished Obstetricians and Gynecologists and American nationals, who are among us on the occasion of the Third Inter-American Meeting of the American College of Surgeons, a subject that lends itself to hear valuable opinions to clarify concepts and can sit guidelines for proper practice of modern obstetrics. Rather than deal with a particular point of our specialty we have thought better address an issue of broader and doctrine, which expresses the thought of all teachers teaching in our care, such is "Interventionism and absenteeism in Childbirth". By tradition, like Schumann, of Philadelphia, he says Obstetrics is the second oldest specialty, preceded only by thoracotomy practiced Surgery given to Adam, but then came the birth of Cain and Abel that gives the next place. Since ancient times, it was a surgical specialty by the frequency with which manual or operative art had to intervene for delivery when nature alone could not. So we know that the cesarean section abdominal has been practiced for many centuries and later the forceps, version and other operations, but we also know that for a very long period dominated delivery care the patient and unarmed hopes, in the hope that nature resolved in some cases impossible.